C14orf166 is a high-risk biomarker for bladder cancer and promotes bladder cancer cell proliferation. Issue 1 (December 2016) - Chen, Mingkun; Ye, Yunlin; Zou, Baojia; Guo, Suping; Zhou, Fangjian; Lu, Keshi; Liu, Jianye; Xu, Zhenzhou; Han, Hui; Liu, Zhuowei; Li, Yonghong; Yao, Kai; et al.
Abstract Background C14orf166 (chromosome 14 open reading frame 166) plays a crucial role in some tumors, but its role in bladder cancer hasn't been explored. Method We determined C14orf166 expression in uroepithelial cell, bladder cancer cells, normal bladder tissues and bladder cancer tissues using quantitative RT-PCR and western blot, we then analyzed the correlation between C14orf166 expression and clinicopathologic characteristics in a cohort of 149 patients with bladder cancer. Finally we downregulated C14orf166 and determined its role in the proliferation of bladder cancer cell lines using MTT assay, colony formation assay and cell cycle assay. Results We demonstrated C14orf166 was upregulated in bladder cancer cells and tissues, C14orf166 expression was significantly correlated with larger tumor size (P = 0.001), lymph node involvement (P < 0.001), histological differentiation (P < 0.001), survival time and vital states, and high C14orf166 expression correlated with poor survival, these results suggested C14orf166 served as a high-risk marker for bladder cancer. Knockdown of C14orf166 decreased the proliferation rate and colony formation ability of bladder cancer cells, and arrested cell cycle in G1/S transition. Further analysis showed that C14orf166 knockdown caused abnormal expression of key proteins for G1/S transition, such as Cyclin D1, P21, P27 and Rb phosphorylation. Conclusions This study demonstrates that C14orf166 promotes bladder cancer cell proliferation and can be a novel prognostic biomarker for patients with bladder cancer.